Chemical Comparative Study of the Chemisorption of Carbon Dioxide in Non-Aqueous and Aqueous Systems - Karimova Feruza Sattarovna; Jurayeva Umida Bahodirovna; Jumaboyev Olim Sharofovich (Genius Publishing Group, 2023)
In this article, the chemical comparison of the chemical absorption of carbon dioxide in non-aqueous and aqueous systems was carried out. Investigation in non-aqueous systems 2-amino 2-methyl-1-propanol in aqueous medium used by MEA
Keywords: Mea; carbon dioxide; non-aqueous and aqueous systems; dimethyl sulfoxide